Prognostic potential of fusion gene analysis using plasma cell-free RNA in malignant bone and soft tissue tumours - Naoki Furukawa; Nobuhiko Hasegawa; Daisuke Kubota; Yasuhiro Nakamura; Hirokazu Tanaka; Shintaro Iwata; Akira Kawai; Tsuyoshi Saito; Tatsuya Takagi; Shinji Kohsaka; Muneaki Ishijima (BMC Cancer)
Abstract Background Liquid biopsy, which facilitates minimally invasive analysis of body fluid samples, has considerable potential as a diagnostic and prognostic tool in various cancers. Analysis of circulating tumour cells, circulating tumour DNA, and exosomes in liquid biopsies has advantages and disadvantages. However, their utility in rare cancers, such as malignant bone and soft tissue tumours, remains unknown. In this study, we examined the levels of circulating cell-free tumour RNA (cfRNA) in the blood of patients with malignant bone and soft tissue tumours harbouring specific fusion genes, to explore the relationship between fusion gene expression in the blood and therapeutic response and disease status, and to validate the clinical utility of liquid biopsy. Methods The study involved 3 cases (7 samples) of Ewing’s sarcoma, 6 cases (12 samples) of myxoid liposarcoma, and 1 case (2 samples) of synovial sarcoma with specific fusion genes. Fusion gene analysis was performed using tumour tissue samples to identify breakpoints. Primers for liquid biopsy were designed based on the fusion genes identified. cfRNA was extracted from each patient’s plasma and used for reverse transcription polymerase chain reaction (RT-PCR) with the designed primers. The RT-PCR product was subjected to Sanger sequencing. Results Fusion gene breakpoints were identified in 10 samples from 6 cases. The fusion gene detection rate in the blood was 100% at both naïve status and symptom exacerbation in patients with Stage IV disease. In patients with Stage III disease progressing to Stage IV, the fusion gene was detected in the blood prior to imaging tests. Conclusions The detection of specific fusion genes from cfRNAs shows potential for monitoring the progression of fusion-related sarcomas in the context of chemotherapy.